Hubungan Shalat Fardu Berjamaah Dengan Kecerdasan Emosional Pada Jamaah Mesjid Al Jihad Banjarmasin - Ahmad Jauhari; Asmaran AS; Siti Faridah (Faculty of Ushuluddin and Humanities, 2017)
Al Jihad Mosque Banjarmasin is a mosque that is identical with Muhammadiyah, this mosque is followed by many pilgrims and loyal at the time of the implementation of prayers fardu congregation. Jamaah consists of various groups regardless of background, both in terms of age, economy, organization and even the sick pilgrims (post-stroke) are actively involved in congregation. Active Jamaat prayers in congregation do not only come from residents around the mosque complex, but also many pilgrims who come from outside the mosque complex, even the distance difference between their residence with the mosque a few kilometers. In heavy rainy weather conditions, they still enthusiastically follow the prayers in congregation fardu mosque. In addition, there are things that are felt by pilgrims such as comfort, tranquility of heart and mind, emotional stability, silaturrahim which all is related to emotional intelligence.In this study, the main problem is how is the relationship of prayer in congregation with emotional intelligence in the congregation of Al Jihad Mosque Banjarmasin ?. The method used is quantitative and qualitative descriptive method with methodological arrangement such as approach and type of research, research location, population and sample, data and data source, procedure and data collection, quantitative and qualitative technical data analysis.The result of the study found that there is a correlation between salat fardu congregation with emotional intelligence, this is proved by the data from questionnaires from 30 pilgrims (respondents) that is: able to control the impulse of worldly lusts with the highest opinion is 60% said yes and 40% stated sometimes .Motivating yourself with the highest opinion is 90% states yes and 10% states sometimes. Able to survive in the face of trials with the highest opinion is 86.67 states yes and 13, 33 states sometimes. No exaggeration with the highest opinion is 90% states yes and 10% states sometimes. Being able to set the mood with the highest opinion is 86.33% and 13.33 states sometimes. Keeping the stress burden does not cripple the thinking ability with the highest opinion is 90% states yes and 10% states sometimes. The ability to empathize and pray with the highest opinion is 90% say yes and 10% say sometimes.